Peningkatan kinerja pelayanan publik melalui peningkatan motivasi spiritual - Mujib Mujib; Denok Kurniasih; Ali Rokhman (Masyarakat, Kebudayaan dan Politik, 2016)
Officer's performance in Regional Disaster Relief Agency (Badan Penanggulangan Bencana Daerah) Kebumen Regency, based on the existing data in the field, is not yet optimum. This circumstance was related to threefactors namely ability, working discipline, and spiritual motivation. This research aimed to analyze the influence of ability, working discipline, and spiritual motivation toward officers performance in BPBD of Kebumen Regency. The research method used was quantitative analysis, the data obtained by givingquestionnaire, answers were analyzed by multiple linier regression to determine the relations between independent variables: the ability, working discipline, and spiritual motivation with the dependent variable wasperformance. After analyzing three variables, it was found that performance of Civil Servant on Regional Disaster Management Agency Kebumen was good. The result showed that the ability (X1) influenced performance of Civil Servant on Regional Disaster Management Agency Kebumen with percentage of 37.7%;working discipline (X2) influenced performance of Civil Servant on Regional Disaster Management Agency Kebumen with percentage of 72.3%; spiritual motivation infuenced performance of Civil Servant on Regional Disaster Management Agency Kebumen up to 66.1%. The result also showed positive relations between three variables, as those variables were impactful in significant way. Finally; ability, working discipline and spiritual motivation influenced overall performance of Civil Servant on Regional Disaster Management Agency Kebumen up to 78.3%. It means that the greater level of ability, working discipline and spiritual motivation resulted to a greater level performance of Civil Servant on Regional Disaster Management Agency Kebumen, and vice versa.